Identifying hypoprolific boars by examining production records - Zhang, TQ; Marsh, WE; King, VL (Journal of Swine Health and Production, 1996)
Analysis of litter size performance of 4388 boars used in single-boar matings revealed that 191 (4.3%) were hypoprolific according to the criteria of Popescu. Boars classified as normal had sired litters with an average liveborn litter size of 9.984 +/- 0.016 standard error (SE) piglets compared to 7.762 +/- 0.05 7 SE (P < 0.0001) for the hypoprolific boars (HPB), a mean reduction of 2.22 piglets. Also, the average number of piglets born dead was significantly greater for the hypoprolific boars as compared to the normal boars (1.0236 +/- 0.0309 SE versus 0.9138 +/- 0.0085 SE; P= 0.0004). Based on our findings we propose an improved definition of hypoprolificacy based on that of Popescu.These data suggest that herd average litter size could be increased substantially by identifying and culling suspected hypoprolific boars as early in their careers as possible, based on farrowing records following single-boar matings. We present a discussion of the necessary number of farrowing records required to do this at various levels of confidence. Since up to half of hypoprolific boars may have a heritable chromosomal abnormality known to cause small litters, we suggest that cytogenetic examinations of hypoprolific boars be the first step in investigating this malady.
Keywords: swine; hypoprolific; boars; reproduction; records